Effects of Yucca schidigera extract on serum biochemical parameters, humoral immune response, and intestinal health in young pigeons - Sun, Xiaoshan; Wang, Zheng; Li, Xing; Du, Shaohua; Lin, Dongmei; Shao, Yuxin (Frontiers in Veterinary Science, 2023)
This study was conducted to investigate the effects of Yucca schidigera extract (YSE) on growth performance, serum biochemical parameters, immune function, intestinal morphology, and microbiota diversity of young pigeons. A total of 120 healthy White King pigeons (28 days old) with similar weight were randomly assigned to 4 treatments with six replicate cages. Each of the pigeons from 4 treatments was orally administrated with 0 (control), 5, 10, and 15 mg YSE per day, respectively. The results showed that orally supplemental YSE had no significant effects (P > 0.05) on the growth performance and immune organ index of pigeons. The serum total protein and IgM contents in the 10 mg YSE group were significantly higher (P < 0.05) than those in the control group. Supplemental 10 and 15 mg YSE significantly lowered the level of serum total cholesterol (P < 0.05) and increased (P < 0.05) the villi height in the jejunum compared with the control group. Supplemental 5 and 10 mg YSE significantly decreased (P < 0.05) the level of serum alanine aminotransferase and the crypt depth in the ileum compared with the control group. The beta diversity showed a distinct difference in the ileum microbial composition between the control and the 10 mg YES group. YSE supplementation enriched the bacterial genera Sulfurospirillum, Solobacterium, Desulfovibrio, Desulfobulbus, Lactococcus, Parabacteroides, Acidaminococcus, Acetobacter, and Streptococcus. Additionally, Enterococcus genus showed a significantly negative correlation with serum alanine aminotransferase (R = -0.618, P = 0.043). Actinomyces genus showed a significantly negative correlation with cholesterol (R = -0.633, P = 0.036). Turicibacter genus showed a significantly positive correlation with villi height in the jejunum (R = 0.751, P = 0.008). These results indicated that orally supplemental YSE could improve serum biochemistry, immunoglobulin contents, and intestinal morphology by regulating the composition of microbial community in the ileum of young pigeons.